INNOVATIVE SECURITY: THE BASIC CONCEPTS, ESSENCE - V. A. Sakovich; G. M. Brovka (Наука и техника)
Some theoretical and methodological aspects of a role and value of innovative security in system of national security of the state are considered. The basic concepts of innovative security, essence of innovative security in formation of innovative economy, economy of knowledge are analyzed. Questions of innovative security get the special importance because now innovative technologies and processes of their introduction have crucial value for improvement of quality of life, expansion of possibilities of development and maintenance of national security of all without an exception of the states. In the majority of economically developed states already long time researches devoted to problems of national and economic security are conducted. And, the innovative component in these researches is considered as a component economic or scientific and technical (technological) security. The methodology of studying national and economic is in this time developed, security, there was a conceptual device and structure of categories «national security». Recognising importance of the spent workings out on a security problematics, it is necessary to notice that the system research devoted to studying of problems of maintenance of national security in the conditions of innovative development till now it was not spent. Especially it concerns processes of maintenance of interrelation of national security and innovative activity, formation of the concept of innovative security, its realisation in practice. Till now there is no unequivocal interpretation of essence of innovations, their influences on national and economic security. The analysis shows that at transition to an innovative way of development there are changes not only in economy and its making parts, but, and in world outlook, psychological, political, social and economic, scientifically-technological, educational and cultural spheres, institutional structures of the state and a society, in development of the person. That is, the spheres which problems of safe development cannot be solved within the limits of economic security are mentioned. There is an objective requirement, for the decision of these many-sided and multidimensional problems arising in the course of formation of innovative economy, its safe development to generate within the limits of system of national security a new direction innovative security.